Non Penal Efforts to Overcome the Crime of Electricity Theft at PT PLN Persero Main Unit for West Sumatra Region - Dodi, Hendri; Fitriati, Fitriati; Faniyah, Iyah (Greenation Research & Yayasan Global Resarch National, 2023)
The crime of stealing electricity is regulated in Article 362 of the Criminal Code. Non Penal Efforts by PT PLN (Persero) Main Unit for West Sumatra Region in Preventing the Crime of Electricity Theft is by issuing a P2TL (Controlling the Use of Electricity) policy. The research specifications are analytical descriptive, with a normative juridical approach supported by empirical juridical. The data obtained was then analyzed qualitatively . The results of the research are the expertise of PLN field staff personnel and equipping them with adequate facilities and infrastructure so that they can track or detect electricity theft from an early age. The need for socialization to the public regarding the act of electricity theft so that people know the dangers and consequences that can occur from electricity theft.